Image-based MRI detection of brain tumours using convolutional neural networks - Preethi, G; NG, Thangamma; Sankar, S Perumal; Walid, Md Abul Ala; Suganthi, D; Deepthika, K (Review of Computer Engineering Research, 2023)
Rapid and uncontrolled cellular proliferation is what distinguishes a brain tumor. Unfortunately, brain tumors cannot be prevented other than via surgery. As predicted, deep learning may help diagnose and cure brain cancers. The segmentation approach has been widely studied for brain tumor removal. This uses the segmentation approach, one of the most advanced methods for object detection and categorization. To efficiently assess the tumor’s size, an accurate and automated brain tumor segmentation approach is needed. We present a fully automated brain tumor separation method for imaging investigations. The approach has been developed with convolutional neural networks. The Multimodal Brain Tumor Image Segmentation (BRATS) datasets tested our strategy. This result suggests that DL should investigate heterogeneous MRI image segmentation to improve brain tumor segmentation accuracy and efficacy. This study may lead to more accurate medical diagnoses and treatments. Researchers in this study also found a way to automatically find cancerous tumours by using the Grey Level Co-Occurrence Matrix (GLCM) and discrete wavelet transform (DWT) to find features in MRI images. They then used a CNN to guess the final prognosis. The preceding section details this technique. When compared to the other algorithm, the CNN method uses computer resources better.